Antioxidant activity of red rose leaves (Rosa chinensis jacq.) extract - Deviyanthi Nur Afifah; Yessy; Farida Nur Rahmani; Ayu Lia Ningsih; Citra Dewi Puspita Sari; Resna Reformasi Yudapradja; Praptiwi; Rahmawati Ridwan (Indonesian Society for Biochemistry and Molecular Biology, 2020)
Background: Background: Antioxidants are compounds that can neutralize free radical reactions. The red rose leaves (Rosa chinensis Jacq.), usually disposed of as waste, have been shown to have antioxidant activity. Objective: This study aims to determine the antioxidant activity of red rose leaves extracts. Methods: The red rose leaves were extracted by the maceration method in ethanol, methanol, ethyl acetate, and n-hexane. The antioxidant activity was measured by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and was expressed as IC50 and an antioxidant activity index (AAI). Results: The results showed that the red rose leaves ethanol, methanol, ethyl acetate, and n-hexane extracts had an antioxidant activity with an IC50 value of 1.8, 8.7, 210.3, 48.7 µg/mL, respectively, and an AAI value of 17.3, 3.5, 0.1, 0.6, respectively. The main content of ethanol and methanol extracts are flavonoid, saponin, and tannin. Conclusion: The ethanol and methanol extract showed the most potent antioxidant activity.